Efek Pemberian Pupuk Anorganik NPKMg Dan Pupuk Organik Super K Terhadap Pertumbuhan Bibit Kelapa Sawit (Elaeis Guineensis Jacq) Umur 7 – 13 Bulan - Noviyanti, Fauli; Khoiri, M. Amrul; Yoseva, Sri (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2021)
This study aims to determine the effect of giving inorganic fertilizer NPKMg and organic super K fertilizer and to get the best combination dose of inorganic fertilizer NPKMg and organic super K fertilizer on the growth of oil palm seedlings at the age of 7 months. This research was conducted for 6 months starting from October 2020 to April 2021. Using a factorial Completely Randomized Design (CRD). The first factor is inorganic fertilizer NPKMg with 2 levels, namely A1: 7.5 g per polybag, A2: 10 g per polybag. The second factor is super K organic fertilizer with 3 levels, namely K1 : 6.25 g per polybag, K2 : 12.5 g per polybag, K3 : 18.75 g per polybag. Parameters observed were plant height, number of midribs, leaf width, leaf length and bulb circumference. The data obtained were analyzed statistically using analysis of variance and further tested with Duncan's New Multiple Range Test (DNMRT) level 5% using the SPSS application. The results showed that the application of inorganic fertilizer NPKMg 10 g per polybag was able to increase the growth of oil palm seedlings in the main nursery. Application of organic fertilizer super K 12.5 g per polybag was able to increase the growth of oil palm seedlings. The combination of inorganic fertilizer NPKMg 10 g per polybag and organic fertilizer super K 12.5 g per polybag gave the best results for the growth of oil palm seedlings.Keywords: NPKMg inorganic fertilizer, super K organic fertilizer, oil palm seedlings